FORMULASI SEDIAAN LIP BALM KULIT MANGGIS (Garcinia mangostana L.) SEBAGAI ANTIOKSIDAN - Sakna Binta Munaya; Endang Setyowati; Fahrudin Arif (Yayasan Nusantara Hasana Berdikari, 2025)
Lip balm is a cosmetic preparation designed to help protect, nourish, and moisturize the lips. This study utilizes mangosteen peel extract (Garcinia mangostana L.), which is rich in antioxidants, as the active ingredient in lip balm formulations. The aim of the study is to evaluate the physical quality and antioxidant activity of five lip balm formulas containing varying concentrations of mangosteen peel extract (10%, 15%, 20%, 25%) and one comparison formula containing 10% vitamin C. Physical quality tests included organoleptic evaluation, homogeneity test, and pH measurement. In addition, antioxidant activity was assessed using the DPPH method, along with skin irritation and user preference tests. The results showed that all lip balm formulas exhibited good organoleptic characteristics and homogeneity, with pH values ranging from (4.5 to 6.5). Irritation tests revealed no negative skin reactions. User preference tests indicated that Formulas F3 and F4 were the most favored in terms of texture, aroma, and comfort of use. The highest antioxidant activity was observed in Formula F5 (IC₅₀ = 46.6 µg/mL), followed by F4 (64.3 µg/mL), F3 (101 µg/mL), F2 (112 µg/mL), and F1 (113 µg/mL). These findings demonstrate that mangosteen peel extract can be successfully formulated into lip balm products that meet physical quality standards and exhibit significant antioxidant activity. The formula containing 25% extract (F4) showed the most optimal overall performance among the tested formulations.